KARAKTERISASI DAN PREPARASI SENSOR BERBASIS KITOSAN SEBAGAI DETEKTOR PENYAKIT DIABETES - Juan Randy Simamora; Iskandar Iskandar; Aroli Harefa; Gusnita Betaria Sinaga (Universitas Quality, 2021)
Characterization and preparation of chitosan-CMC films have been carried out in detecting diabetes. The characteristics of the chitosan-CMC film are able to detect blowing acetone levels out of the human breath, indicated by the unstable electrical properties of the output voltage between patients and non-sufferers. Acetone itself is a substance produced when metabolic processes take place in the body. Voltage increases due to the influence of imperfect metabolic processes, so diabetics produce excessive levels of acetone. The sensor film was modified chitosan-CMC, with varied mass composition of 0.5 g: 0.1 g, 0.5 g: 0.5 g. Chitosan-CMC film was fabricated using the electrodeposition method. The chitosan-CMC film characteristics of 0.1 gr and 0.5 gr from the fabrication and measurement process of PSA obtained 3,716.34 nm and 5,129.97 nm. The FT-IR test results of 0.1 g and 0.5 g of chitosan-CMC showed a change in the relationship between different functional groups. The UV-Vis test obtained a different maximum absorbance for each chitosan-based sensor with a composition of Cs-CMC 0.5 w / v, Cs-CMC 0.1 w / v, respectively 0.114167 (427 nm), 0.098258 ( 417nm). It shows that the chitosan-CMC based sensor with the addition of 0.5 g of CMC has a very high sensitivity concentration. Chitosan-CMC sensor film with 0.5 CMC has good characteristics, on a very even film surface, has high thermal properties and an energy gap of 3.87 eV.